The future of urban mobility in german cities. People, access and environment. - Kodukula, Santhosh (Sunny) (Steiner, 2017)
The article discusses the future urban mobility in Germany based on the scenarios from various organisations and deliberate on the projects that will accelerate German cities towards a low carbon future, whilst implementing an integrated, inclusive and innovative urban mobility system.
Keywords: Stadtentwicklung; Stadtverkehr; Verkehrskonzept; Mobilität; Umweltverträglichkeit; Integrierte Verkehrspolitik; Nachhaltige Mobilität